2018
DOI: 10.21470/1678-9741-2017-0214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Level of Vitamin D on Postoperative Atrial Fibrillation in Patients Undergoing Isolated Coronary Artery Bypass Grafting

Abstract: ObjectivePostoperative atrial fibrillation (PoAF) is a common complication after coronary artery bypass grafting (CABG). The aim of the present study was to evaluate the association between development of PoAF and vitamin D levels in patients undergoing isolated CABG.MethodsThis prospective randomized clinical trial was conducted on the patients with isolated CABG. The study was terminated when 50 patients in both PoAF(+) group and PoAF(-) group were reached. Development of AF until discharge period was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
0
21
1
2
Order By: Relevance
“…VitD deficiency is independently associated with cardiovascular morbidity and mortality in the general population [1] . Growing evidence demonstrates that vitD deficiency is strongly associated with various cardiovascular diseases, including postoperative atrial fibrillation and increased frequencies of HT, DM, obesity, HL, metabolic syndrome, and inflammation [2-6,17,18] . Several potential mechanisms established associations between vitD and atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%
“…VitD deficiency is independently associated with cardiovascular morbidity and mortality in the general population [1] . Growing evidence demonstrates that vitD deficiency is strongly associated with various cardiovascular diseases, including postoperative atrial fibrillation and increased frequencies of HT, DM, obesity, HL, metabolic syndrome, and inflammation [2-6,17,18] . Several potential mechanisms established associations between vitD and atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies with 5503 cases/66,139 participants were included [7, 9, 12, 13, 16, 18]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In subsequent studies, he found out that vitamin D supplementation can prevent the occurrence of POAF when vitamin D is extremely deficient [22] . The other four studies supported that vitamin D deficiency directly led to an increased incidence of POAF [23-26] . The patients enrolled in the study by Gode et al [25] and Özsin et al [26] were young, and all studies supported a left atrial diameter as an independent risk factor for POAF.…”
Section: Epidemiological Researchmentioning
confidence: 99%
“…The other four studies supported that vitamin D deficiency directly led to an increased incidence of POAF [23-26] . The patients enrolled in the study by Gode et al [25] and Özsin et al [26] were young, and all studies supported a left atrial diameter as an independent risk factor for POAF. Overall evidence of vitamin D deficiency seems to support the onset of POAF.…”
Section: Epidemiological Researchmentioning
confidence: 99%